Tingkat Kepercayaan Diri Dan Kecemasan Atlet Dayung PPLOP Jateng Selama Latihan Pada Masa Adaptasi Kebiasaan Baru (Indonesian Journal for Physical Education and Sport, 2023)
The situation after the pandemic will have an impact on psychological conditions, namely the confidence and anxiety of Central Java PPLOP rowing athletes while practicing. This research was conducted to find out what happened through a survey method using a cross sectional study. The samples taken were 10 athletes with details of 4 men and 5 women using a total sampling technique. The instruments used using SSCI are 13 items and SAS-2 with 15 question items. Data analysis used descriptive exploration SPSS and crosstab. The results of data analysis of self-confidence in skills and physical training at the age of 15 years are high 8.67, male sex is 8.50, kayak number is 8.80, cognitive age 16 years is high 14.50, male sex is 14.50 , Kayak number 14.80, High 15 year old endurance 14.67, Female gender 14.50, Kayak number 14.40. Low 16 year old somatic anxiety 6.75, Male gender 6.25, Kayak number 7.40, Low 16 year old anxiety 10.25, Male sex 12.75 , Kayak number 11.40, Disorders the concentration of 16 years old is low at 7.50, Male sex is 6.75, Kayak number is 7.20. The conclusion shows that the highest 15-year-old age group is 37.67, the highest female athlete is 37.33 and the highest kayak number is 38, for anxiety the lowest 16-year-old athlete is 24.5, the lowest male athlete is 25.75 and the lowest kayak number is 26.